LEGACY OF SLAVERY IN LEON FOREST’S TWO WINGS TO VEIL MY FACE - Asha P R; Bose, Dr R David Raja; Sunitha, S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Leon Forrest is one of the foremost African American novelists. He has always been concerned with the problem of identity, specifically the fragmented identity of man living in the postcolonial era. Such characterization is evident in his Forest County trilogy. This article attempts to demonstrate the legacy of slavery in Sweetie Reed, Nathaniel Witherspoon, and Angelina in Two Wings to Veil My Face. Social, historical, and psychological factors influence the misery and suffering of these Black slaves. They often engage in the struggle to find out their final image of self as they are entangled in the web of slavery and traumatic experiences of the community’s past.